Implementasi Metode Manhajī Pada Pembelajaran Bahasa Arab (Studi Kasus Di Ranting Muhammadiyah Muntilan Magelang) - Suwahit, Agung, Drs. Najmuddin Zuhdi, M.Ag, Drs. Saifuddin Zuhri, M. Ag (2015)
This adult learning Arabic has been much used as subjects in educational institutions. With so many educational institutions which organizes Arabic language learning, many emerging methods of learning which aims to facilitate the study of Arabic with a relatively short time. One of them is Manhajī method pioneered by M. Anas Adnan, where the object pembelajaranya this method is straight from the verses of the Qur'an. This method is very rapid development since its application is not limited by level of education, so that the general public was mempelajarinnya, as held in the Branch Gaungpring Muntilan Muhammadiyah Magelang, who have applied this method of approximately three years. Application of methods and evaluation in writing is done in the Branch has been very intensive, so the development of the ability of learners in the twigs are very visible. Based on the above background, it can be a formulation of the problem, namely, how the implementation methods in learning Arabic Manhajī in Muntilan Gunungpring Twig Muhammadiyah Magelang and what are the constraints faced ?. Such as where formulation maasalah, the purpose of this study was to describe the implementation of the method Manhajī on learning Arabic at the Branch Gunungpring Muntilan Muhammadiyah Magelang and what are the constraints faced. The benefits of this research is to increase the repertoire and develop knowledge of Arabic language learning and feedback for teachers to address issues relating to methods Manhajī. Data Dalampengumpulan authors use the method of observation, interviews, and documentation. The data were then analyzed with the inductive method. From the research results can be concluded that exercising their Manhaji methods in learning Arabic has several stages. Stages in the study are: (1) the stage of reading, (2) the stage of deciphering said perkata, (3) the stage of understanding the meaning of the verse, (4) the evaluation phase. While the obstacles encountered in the implementation of the method Manhajī on learning Arabic in twigs Gunugpring influenced by two factors, namely internal and external factors.